1999
DOI: 10.1080/00039899909603372
|View full text |Cite
|
Sign up to set email alerts
|

Third-Trimester Amniotic Fluid Metal Levels Associated with Preeclampsia

Abstract: Studies of maternal amniotic fluid and serum at delivery have revealed the presence of toxic metals or deficiencies of essential metals associated with high-risk pregnancy. Essential and toxic metal levels were studied in 29 preeclamptic and 101 normal pregnancies. The authors grouped the samples according to the following gestation ages: 33-36 wk (48 normal and 10 preeclamptic) and 37-40 wk (53 normal and 19 preeclamptic). The metals studied were calcium, magnesium, zinc, selenium, copper, cadmium, and lead. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…21 Amniotic fluid Zn concentrations have also been reported to be decreased in preeclamptic women delivering preterm (33-36 weeks gestation) in a small retrospective cross-sectional study from USA. 22 Over decades, many studies have been conducted to evaluate iron status in pregnancy and its possible contributory role in oxidative stress in preeclampsia, but there were different conclusions. In our study there was no significant difference in maternal age between normal pregnant and preeclamptic women.…”
Section: Discussionmentioning
confidence: 99%
“…21 Amniotic fluid Zn concentrations have also been reported to be decreased in preeclamptic women delivering preterm (33-36 weeks gestation) in a small retrospective cross-sectional study from USA. 22 Over decades, many studies have been conducted to evaluate iron status in pregnancy and its possible contributory role in oxidative stress in preeclampsia, but there were different conclusions. In our study there was no significant difference in maternal age between normal pregnant and preeclamptic women.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially significant sources of such contaminants include the amniotic fluid, in which fetal hair is permanently bathed during gestation and known to contain measurable concentrations of trace elements [9][10][11][12][13]. Others include uterine secretions [14], placental and deciduous matter, and maternal blood [15], all of which are likely to come into contact with the fetal scalp, particularly in the event of obstetric complications resulting in hemorrhaging and/or surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A minimal amount is excreted in the urine. Recently, it was reported that elevated Cu concentrations in maternal serum are found in preeclamptic women [11,12,14], although there are also reports in which maternal serum Cu levels were found to be lower in preeclampsia as compared to [10,13]. This finding is supported by the decreasing trend in the level of free estriol (which induces the production of Cu carrying protein) among preeclamptic cases [13].…”
Section: Resultsmentioning
confidence: 78%
“…A few recent reports have shown increasing of Cu concentrations (as the cofactor of antioxidant enzymes) and also oxidant and parameters in preeclamptic pregnant women. It was suggested that Cu demonstrates contrary kinetic behavior during the entire pregnancy as compared with the corresponding zinc values [6,7,10]. Differences in study design, limited statistical power, differences in tissues and analytical techniques used to measure maternal Cu status, as well as differences in exposure to environmental Cu, like different maternal dietary intake, are possible explanations for this change.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation